2022
DOI: 10.1002/jpen.2321
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Controlling Nutritional Status score in predicting the prognosis of patients with lung cancer: A multicenter, retrospective study

Abstract: Background The body's immune‐nutrition status affects prognosis in patients with lung cancer. The Controlling Nutritional Status (CONUT) score is an immune‐nutrition‒related index associated with prognosis in other tumors. We aimed to assess the value of CONUT scores in predicting prognosis in patients with lung cancer. Methods In this retrospective, multicenter study, 1339 patients with lung cancer were divided into low and high CONUT score groups. The relationship between CONUT scores and overall survival (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous studies reported that LCR, 26 ALI, NLR, PLR, 6 SII, 27 CAR, 28 mGPS, 29 CONUT score, 30 AGR, 14 PNI, 31 NRI, GNRI, 32 and CRP 7 were useful as predictors of the prognosis of patients with lung cancer. Consistent with previous studies, Figure 3 The time-dependent ROC of inflammation and nutrition-relative indicators for diagnosing overall survival in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies reported that LCR, 26 ALI, NLR, PLR, 6 SII, 27 CAR, 28 mGPS, 29 CONUT score, 30 AGR, 14 PNI, 31 NRI, GNRI, 32 and CRP 7 were useful as predictors of the prognosis of patients with lung cancer. Consistent with previous studies, Figure 3 The time-dependent ROC of inflammation and nutrition-relative indicators for diagnosing overall survival in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that LCR, 26 ALI, NLR, PLR, 6 SII, 27 CAR, 28 mGPS, 29 CONUT score, 30 AGR, 14 PNI, 31 NRI, GNRI, 32 and CRP 7 were useful as predictors of the prognosis of patients with lung cancer. Consistent with previous studies, our study found that PLR, ALI, NLR, SII, CAR, CONUT score, mGPS, GNRI, AGR, PNI, NRI, LCR, and CRP were all associated with OS in univariate analysis; each of these indicators except the PLR was an independent prognostic indicators of lung cancer patients and that GLR, mGNRI, and LCS, which were not examined in previous study, were also independent predictors of prognosis in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that the TNM stage, age, sex, and PG‐SGA were the mediating factors that contributed the most. TNM stage is currently a clinically accepted index for evaluating tumor progression, and its grading needs to be determined based on postoperative pathology and systemic examination, which are more limited in use 24–26 . Age and sex are natural factors that cannot be changed.…”
Section: Discussionmentioning
confidence: 99%
“…TNM stage is currently a clinically accepted index for evaluating tumor progression, and its grading needs to be determined based on postoperative pathology and systemic examination, which are more limited in use. 24 , 25 , 26 Age and sex are natural factors that cannot be changed. As age increases, the incidence of cancer increases, and physical function decreases, leading to a poor patient prognosis and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…By applying the COUNT score, clinicians can easily and comprehensively assess nutritional status. At present, extensive research supports the important role of the CONUT score in the prognosis of gastric cancer, esophageal cancer, lung cancer, hepatocellular carcinoma, and other surgical tumors (20)(21)(22)(23)(24). In recent years, CONUT scores have also shown good effects in predicting short-term postoperative complications (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 96%